1994
DOI: 10.1161/01.cir.90.2.735
|View full text |Cite
|
Sign up to set email alerts
|

Histological alterations in chronically hypoperfused myocardium. Correlation with PET findings.

Abstract: Background In patients with chronic coronary artery disease (CAD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
77
1
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(96 citation statements)
references
References 41 publications
12
77
1
6
Order By: Relevance
“…Human hibernating myocardium has a distinctive histological appearance with myolysis, glycogen accumulation, and increased interstitial fibrosis (Fig 3). 134,[152][153][154] It has been suggested that these histopathological changes may represent a dedifferentiation of the myocytes. 153 When advanced, such changes indicate a poor prognosis for recovery even with adequate revascularization.…”
Section: Detecting Hibernating Myocardiummentioning
confidence: 99%
“…Human hibernating myocardium has a distinctive histological appearance with myolysis, glycogen accumulation, and increased interstitial fibrosis (Fig 3). 134,[152][153][154] It has been suggested that these histopathological changes may represent a dedifferentiation of the myocytes. 153 When advanced, such changes indicate a poor prognosis for recovery even with adequate revascularization.…”
Section: Detecting Hibernating Myocardiummentioning
confidence: 99%
“…After revascularisation, the hibernating segments often show a delayed recovery of function which can take a few months to more than one year in a fraction of patients with chronic hibernating myocardium [8]. It has been suggested that the structural remodelling found in chronic hibernating myocardium is at least partially responsible for this delayed recovery of function [9][10][11]. In recent studies we have also characterized the dedifferentiation process in an in vitro model by co-culturing adult rabbit CM's with cardiac fibroblasts [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Histological and electron microscopic examination of biopsy material obtained from hibernating regions reveal a variable degree of fibrous tissue replacement, with a proportion of the myocytes showing depleted contractile material, numerous and small mitochondria, and irregular nuclear envelopes. 3,4 Although early studies suggested that such altered myocytes characterized the hibernating state 3 and could explain the delay in recovery in contractile function after successful revascularization, 5 more recent reports have described them in equal frequency in both hibernating and nonhibernating ventricular segments. 4,6 Similar cellular features have also been described in ventricular specimens from patients with dilated, nonischemic cardiomyopathy 7 as well as in rat cardiac myocytes after a short period of unloading.…”
mentioning
confidence: 99%
“…3,4 Although early studies suggested that such altered myocytes characterized the hibernating state 3 and could explain the delay in recovery in contractile function after successful revascularization, 5 more recent reports have described them in equal frequency in both hibernating and nonhibernating ventricular segments. 4,6 Similar cellular features have also been described in ventricular specimens from patients with dilated, nonischemic cardiomyopathy 7 as well as in rat cardiac myocytes after a short period of unloading. 8 It can therefore be hypothesized that these are secondary features of cells contracting against a low afterload and are not characteristic of hibernation.…”
mentioning
confidence: 99%